PERANAN GURU PEMBIMBING DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS UNGGUL DI SMP N 14 PADANG - Ramadhany, Dina Dayu Sintia; Syarif, Mellyarti; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
Problems in the research are the role of mentor teachers in improving student learning outcomes superior class. This study aims to reveal: (1) The role of a tutor to improve learning outcomes through the superior grade student guidance and counseling services, (2) The role of a tutor to improve learning outcomes of students excel class through increased motivation to learn. Type of research is descriptive, which describes a situation with what it is. The population in this study was superior grade students VII.A, VIII.B, XI.A, XI.H totaling 123 people. The samples in this study were drawn from the population, and therefore the sample collection techniques, namely: proportional randomsampling, samples are drawn proportional to the number of population in each class has been defined and numbered 30 people. Data results of the study were processed using techniques percentage. The research found that the role of a tutor to improve learning outcomes through the superior grade student guidance and counseling services classified in either category (73.3%) and the role of tutor to improve learning outcomes through the superior grade students learning motivation belong to the poor category (93.3%). The authors suggested that counselors and teachers all teachers who teach in Padang for SMP N 14 does not distinguish between whether or not a superior grade excels in the provision of counseling services, because each learner has the right to the same education.